Massive pleural effusion and bronchopleural fistula in Wegener’s granulomatosis - Koyama, S.; Murakami, K. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Wegener’s granulomatosis (WG) is characterized by systemic granulomatous necrotizing vasculitis, primarily affecting the respiratory tract and kidneys.We describe a rare case in a 28-year-old woman withWG, presenting with a massive lateral pleural effusion, accompanied by an aseptic bronchopleural fistula formed during immunosuppressive treatment. Although any organ can be involved in WG, only left pleuritis and a purpuric lesion on the neck were detected in this case.The pleural effusion and bronchopleural fistula resolved following immunosuppressive treatment for six months. Thus,WG should be considered in the differential diagnosis of a massive pleural effusion, and fistula formation is a possible complication of treatment.Moreover, immunosuppressive treatment was sufficient to resolve the massive pleural effusion and fistula formation without infection (120 words).